2011
DOI: 10.5194/amt-4-2153-2011
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of internal gravity wave parameters from radio occultation retrievals of vertical temperature profiles in the Earth's atmosphere

Abstract: Abstract.A new method for the reconstruction of internal gravity wave (IGW) parameters from a single vertical temperature profile measurement in the Earth's atmosphere has been developed. This method does not require any additional information not contained in the profile and may be used for the analysis of profiles measured by various techniques. The criterion for the IGW identification has been formulated and argued. In the case when this criterion is satisfied, then analyzed temperature fluctuations can be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 45 publications
0
18
0
15
Order By: Relevance
“…Wang and Alexander (2010) and McDonald (2012), analyzing collocated temperature profiles from COSMIC observations, showed that in the stratosphere, the most large-scale dominant temperature perturbations are of wave nature. Gubenko et al (2008Gubenko et al ( , 2011 developed a method for the determination of the basic characteristics of dominant IGWs, including their intrinsic frequency and phase velocities from vertical profiles of temperature. The method was validated on high-resolution radiosonde observations of temperature and wind and then applied to the analysis of IGWs based on temperature profiles retrieved from RO observations in COSMIC and CHAMP missions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang and Alexander (2010) and McDonald (2012), analyzing collocated temperature profiles from COSMIC observations, showed that in the stratosphere, the most large-scale dominant temperature perturbations are of wave nature. Gubenko et al (2008Gubenko et al ( , 2011 developed a method for the determination of the basic characteristics of dominant IGWs, including their intrinsic frequency and phase velocities from vertical profiles of temperature. The method was validated on high-resolution radiosonde observations of temperature and wind and then applied to the analysis of IGWs based on temperature profiles retrieved from RO observations in COSMIC and CHAMP missions.…”
Section: Discussionmentioning
confidence: 99%
“…The stability of GPS signals, complemented with its global coverage and high vertical resolution, draws the attention of researchers to the study of inhomogeneities in atmospheric refractivity in addition to the retrieval of mean profiles (Belloul and Hauchecorne, 1997;Gurvich et al, 2000;Tsuda et al, 2000;Wang and Alexander, 2010;Cornman et al, 2004Cornman et al, , 2012Shume and Ao, 2016;Gubenko et al, 2008Gubenko et al, , 2011. Occultation-based methods of sounding atmospheric inhomogeneities have a long and successful history.…”
Section: Introductionmentioning
confidence: 99%
“…The GPS-RO has produced highly accurate atmospheric profiles, significantly improving the weather forecasting performance and providing long-term stable references for climate applications (e.g., Anthes 2011;Ladstädter et al 2015). In addition, GPS-RO temperature profiles with superior height resolutions provide a unique opportunity to study the mesoscale temperature fluctuations caused by atmospheric waves in the stratosphere (Alexander et al 2008;Tsuda et al 2011), and analysis of internal gravity wave parameters (Gubenko et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Using this theory we are treating the wave packets as particles moving along rays (Sutherland, 2010) and using the WKB approximations we can relate the wave frequency to a wave's spatial characteristics and background atmosphere properties through a dispersion relation as shown by Fritts and Alexander (2003). Polarization relations used for the determination of the IGWs' parameters from temperature or density profile as proposed by Gubenko et al (2011) are also a product of WKB approximations.…”
Section: Data Description and Methodologymentioning
confidence: 99%